Bi‐level deep mutual learning assisted multi‐task network for occluded person re‐identification. Issue 4 (18th November 2022) - Wang, Yi; Wang, Liangbo; Zhou, Yu
Abstract: An occluded person re‐identification (ReID) approach is presented by constructing a Bi‐level deep Mutual learning assisted Multi‐task network (BMM), where the holistic and occluded person ReID tasks are treated as two related but not identical tasks. This is inspired by the human perception characteristic that there exist both similarities and differences when human views a holistic image and the occluded one. Specifically, a multi‐task network with two branches is designed, where the convolutional neural network based feature representation part shares the weights by two tasks for commonality extraction, while the following output layers have respective weights for difference representation. Furthermore, as the non‐occluded regions convey discriminative information, a bi‐level mutual learning strategy is proposed and applied mutually on two branches to obtain more effective information from the non‐occluded regions in the occluded images for better identity recognition. This is achieved by both feature‐level and output‐level mutual loss functions. Extensive experiments prove the advantages of the BMM for person ReID.